1994
DOI: 10.1007/bf00211019
|View full text |Cite
|
Sign up to set email alerts
|

Apparent regression of the CGG repeat in FMR1 to an allele of normal size

Abstract: The fragile X syndrome is the result of amplification of a CGG trinucleotide repeat in the FMR1 gene and anticipation in this disease is caused by an intergenerational expansion of this repeat. Although regression of a CGG repeat in the premutation range is not uncommon, regression from a full premutation (> 200 repeats) or premutation range (50-200 repeats) to a repeat of normal size (< 50 repeats) has not yet been documented. We present here a family in which the number of repeats apparently regressed from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In Figure 2 it is evident that, in transmissions from mothers in the 50-100 repeat range, the size of the repeat tends to increase steeply, but some contractions were also observed. The contraction of CGG repeat size is not unusual, and was reported in other studies Rousseau et al, 1991;Snow et al, 1993;Vits et al, 1994;Loesch et al, 1995], where reductions were observed within both the premutation and full-mutation ranges, or from full mutation to the premutation, or from the premutation to the normal range. Figure 2 also shows that for mothers with CGG values greater than 100, the number of repeats expands at a rate that seems independent of the size of the mother's CGG repeat.…”
Section: Exploratory Analysissupporting
confidence: 64%
“…In Figure 2 it is evident that, in transmissions from mothers in the 50-100 repeat range, the size of the repeat tends to increase steeply, but some contractions were also observed. The contraction of CGG repeat size is not unusual, and was reported in other studies Rousseau et al, 1991;Snow et al, 1993;Vits et al, 1994;Loesch et al, 1995], where reductions were observed within both the premutation and full-mutation ranges, or from full mutation to the premutation, or from the premutation to the normal range. Figure 2 also shows that for mothers with CGG values greater than 100, the number of repeats expands at a rate that seems independent of the size of the mother's CGG repeat.…”
Section: Exploratory Analysissupporting
confidence: 64%
“…In fragile X syndrome, in which genotype-phenotype correlations have been thoroughly analyzed, at least 5 factors are known to affect the phenotypic expression of the mutation: sex of the affected individual, repeat length (including repeat contractions [159][160][161] ), the pattern of X-inactivation (for females), somatic cell mosaicism, and methylation status of the CpG island adjacent to the repeat. 162 These factors have a profound affect on the clinical phenotype and patterns of inheritance.…”
Section: Expansion Mutation and Nonmendelian Geneticsmentioning
confidence: 99%
“…Reduction of a premutation to a smaller premutation has been detected (6.7,15-17) as well as reduction of a premutation to a repeat length within the normal range (18). Decrease from a full mutation to a premutation has been reported only once (15), whereas the reverse mutation, from full mutation to a normal allele has not yet been described.…”
Section: Introductionmentioning
confidence: 99%